Postpartum maternal separation anxiety, over-protective parenting and children’s social-emotional well-being: Longitudinal evidence from an Australian cohort - D'Esposito, F; Crawford, S; Cooklin, A R; Nicholson, J; Giallo, R (My University, 2013)
Postpartum maternal separation anxiety refers to a mothers' experience of worry and concern about leaving her child for short-term separations. The long-term effects of high maternal separation anxiety on maternal parenting behaviors and child outcomes have been not been established empirically. The aim of this study was to ascertain the prospective relationships between maternal separation anxiety during the child's first year of life, and overprotective parenting and children's social and emotional functioning at age 2-3 years. Structural equation modeling with a large representative cohort of Australian mother-child dyads (N = 3,103) indicated that high maternal separation anxiety was associated with more overprotective parenting behaviors and poorer child socioemotional functioning at age 2-3 years. Findings suggest women with high postpartum maternal separation anxiety may sustain this vigilance across the first years following birth, promoting overprotective behaviors, and resulting in increased behavior problems in their children. Support for women around negotiating separation from their children early in parenthood may prevent the establishment of a repertoire of parenting behaviors that includes unnecessarily high vigilance, monitoring, and anxiety about separation.
Journal of Family Psychology
Keywords: Stress -- Parenting stress; Families -- Mothers; Children -- Outcomes; Child Development -- Emotional; Childhood and child development; Families and relationships; Families; Child Development; Children; Stress; Emotional; Outcomes; Parenting stress; Mothers; Families and relationships; Childhood and child development